Identifikasi Pengembangan Teknologi Tepat Guna Pada Usaha Mikro, Kecil, dan Menengah Di Kota Tarakan - Deny Murdianto; Marhadi Budi Waluyo; Andi Ard Maidhah; Yosef Alexander Koli; Darmawan Darmawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Production tools play an important role in determining the quantity and price of products or services produced by business actors. With the availability of adequate production tools, micro, small and medium enterprises can increase the amount of production in a more efficient time. Apart from updating production tools to sophisticated and modern tools, appropriate technology is one solution that can be used to reduce production costs. This study aims to identify the extent to which micro, small and medium enterprises in Tarakan City understand and utilize appropriate technology in running their business. In this study, a study was carried out related to the means of production used by micro, small and medium enterprises in Tarakan City. In the initial stage, a survey was conducted on the use of production equipment currently in use. Observation of the effectiveness and efficiency of production equipment is the next stage in this study. The production tools used by micro, small and medium enterprises are still using traditional equipment. With traditional tools, they feel they are able to meet sales targets. Some micro business actors also seem unwilling to update production equipment because they are worried about the increase in production costs.